2018
DOI: 10.1186/s12948-018-0102-y
|View full text |Cite
|
Sign up to set email alerts
|

Markers of atopic dermatitis, allergic rhinitis and bronchial asthma in pediatric patients: correlation with filaggrin, eosinophil major basic protein and immunoglobulin E

Abstract: BackgroundAllergic reactions have been implicated as contributions in a number of atopic disorders, including atopic dermatitis (AD), allergic rhinitis (AR) and bronchial asthma (BA). However, the potential for filaggrin protein, eosinophil major basic protein (MBP) and immunoglobulin E (IgE) to elicit allergic response or to contribute to atopic disorders remains largely unexplored in pediatric patients. This study was undertaken to investigate the status and contribution of filaggrin protein, eosinophil MBP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 33 publications
5
13
0
1
Order By: Relevance
“…As a whole, the present findings clearly suggest the roles of multiple proteins in the pathogenesis of BA, AR and AD. Our results are fully supported by numerous studies performed in different disorders including allergic disorders (31)(32)(33)(34). In our previous studies we have also reported pathogenic effects of multiple proteins in patients with systemic lupus erythematosus (35)(36)(37).…”
Section: Discussionsupporting
confidence: 88%
“…As a whole, the present findings clearly suggest the roles of multiple proteins in the pathogenesis of BA, AR and AD. Our results are fully supported by numerous studies performed in different disorders including allergic disorders (31)(32)(33)(34). In our previous studies we have also reported pathogenic effects of multiple proteins in patients with systemic lupus erythematosus (35)(36)(37).…”
Section: Discussionsupporting
confidence: 88%
“…Activated eosinophils in turn also secrete cytokines and chemokines, such as IL-16, IL-12, TGF-β1, and IL-13 and induce immunological reactions. Eosinophil granular proteins deposition and its degranulation observed in AD patients [166]. Topical calcineurin inhibitors like tacrolimus, pimecrolimus, immunomodulatory agents prednisolone, systemic steroid-sparing agents azathioprine, methotrexate, cyclosporine, mycophenolate are available treatments for AD [167,168].…”
Section: Atopic Dermatitis (Ad) or Eczemamentioning
confidence: 99%
“…It has been reported that granuloma eosinophils are highly activated and produce the majority of Th2 cytokines in granulomatous inflammation, which may be important determiners of immunopathology in murine schistosomiasis caused by S. mansoni (6). The eosinophil granulocytes contain four major proteins, i.e., eosinophil cationnic protein [ECP; (7)], eosinophil peroxidase [EPO; (8)], eosinophil protein X (EPX)/eosinophil-derived neurotoxin (9), and major basic protein [MBP; (10)]. Eotaxin is an essential regulator of eosinophil trafficking during healthy conditions (11) and inflammation (12).…”
Section: Introductionmentioning
confidence: 99%